A NEW PROGRAM IN IASI CITY- PUBLIC ACCESS DEFIBRILLATION - Diana Cimpoeşu; Ovidiu Popa; Luciana Rotaru; Antoniu Petriş (Romanian Society of Oral Rehabilitation, 2014)
Public-access automated external defibrillators (AEDs) can seem near-miraculous in their ability to pull sudden cardiac arrest victims back from death, in case of cardiac arrest with Ventricular Fibrillation/ Ventricular Tachycardia. Their use, both medical and public, according to the European Resuscitation Council 2010 Guidelines, highly varies among the European Union and is limited in Romania, especially for public access. In this context, the medical emergency services from Iasi realized a study in order to identify the areas of the city with the highest frequency of cardiac arrest and to propose to local authorities purchasing a number of AEDs and locate them in public places. The project was accompanied by a training program for users without the basic medical training. The project of investing in this type of devices (as European trend) was successful and the model can be follow by others Romanian local and national authorities, for many public sites.